Cybernetic-Existentialism. Issue 1 (2nd January 2016) - Dixon, Steve
ABSTRACT: A theory of Cybernetic-Existentialism is proposed in the light of emerging themes within contemporary arts and performance that appear to relate simultaneously to both fields and to fuse them. Cybernetic-Existentialist ideas are also increasingly prevalent within everyday life and popular culture, and the Disney film Frozen (2013) is examined as an illustration. Case studies are presented of performances by The Wooster Group, Societas Raffaello Sanzio, Jennifer Ringley, Paul Sermon, and Steve Dixon, and analysed with reference to the concepts and innovations of cyberneticians including Gregory Bateson and Existentialist philosophers including Jean-Paul Sartre and Gabriel Marcel. A number of philosophical notions are explored, including Bateson's 'the difference that makes a difference', Marcel's disponibilité (availability), and Sartre's discourses on 'the look', Nothingness, and being-for-others . The argument highlights the complementary and intersecting concerns of cybernetics and Existentialism and how fusing knowledge from these fields can throw light on fundamental issues and developments within arts, culture and everyday life, including interactivity, telepresence, frames, questioning, Angst, and 'separation with communion'.